Pengaruh Implementasi Sistem Mini-QHSE terhadap Tingkat Risiko K3 dan Kesejahteraan Pekerja UMKM: Studi Kuantitatif pada Produsen Tas Anyaman - Syahrial Aman; Moh Daud Ibrohim Sutikno (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study aims to test the effectiveness of the implementation of a simplified Mini-QHSE (Quality, Health, Safety, Environment) system in improving working conditions at the Syams Handicraft woven craft MSME in Pati Regency, Central Java. The study used a quantitative method with a one-group pretest–posttest design involving 47 workers as respondents. Data collection was conducted through questionnaires and observations before and after the twelve-week intervention. The results showed that the implementation of the Mini-QHSE system was able to significantly reduce the level of occupational safety and health risks and significantly improve worker welfare. Further analysis revealed that the Mini-QHSE system made a significant contribution to variations in OHS risks and worker welfare. The dimension of safe work procedures proved to be the most influential factor in reducing work risks, while the training aspect was the main factor in improving worker welfare. Based on these findings, it can be concluded that the Mini-QHSE system designed according to the capacity and characteristics of MSMEs is effective in creating a safer and more prosperous work environment. This model has the potential to be applied to similar MSMEs with contextual adjustments as a practical solution in managing quality, safety, and occupational health in the micro-business sector.